Pemertahanan Bahasa Dayak Kenyah di Kota Samarinda - Kiftian Hady Prasetya; Hani Subakti; Hety Diana Septika (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2020)
The focus of the problem in this study is motivated by the phenomenon of the development of the times and the rapid flow of globalization making the Dayak ethnic in Samarinda City specifically, becoming an ethnic minority so language retention needs to be made in multilingual minority language communities. The language that is the focus of research is Dayak Kenyah Language. The purpose of this study was to determine the factors of preservation of Dayak Kenyah Language in Samarinda City. This research uses descriptive qualitative method with a sociolinguistic approach. The research data were written text (conversational transcripts) from the data source of the Dayak Kenyah ethnic community in Samarinda City. Data collection techniques using the stages of observation, Simak Free Engage Involved (SBLC) techniques, and interviews. Research instruments in the form of devices, stationery, notebooks, and indicators of language maintenance. The results of the study found that there were efforts made by the Dayak Kenyah community in Samarinda City as a manifestation of the language of the Dayak Kenyah region. The research findings are: (1) family factors, (2) social factors, (3) communication intensity factors, (4) activity factors, and (5) desire factors in language retention. The conclusion in this study focuses more on the care and contribution of various layers of ethnic Dayak Kenyah communities, especially in Samarinda, towards the regional languages ​​they have.